2012
DOI: 10.1371/journal.pone.0041998
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of ART Non-Adherence and Delay of ART Initiation among HIV Positive Double Orphans in Kigali, Rwanda

Abstract: BackgroundTo reduce HIV/AIDS related mortality of children, adherence to antiretroviral treatment (ART) is critical in the treatment of HIV positive children. However, little is known about the association between ART adherence and different orphan status. The aims of this study were to assess the ART adherence and identify whether different orphan status was associated with the child’s adherence.MethodsA total of 717 HIV positive children and the same number of caregivers participated in this cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 36 publications
3
50
1
Order By: Relevance
“…For example, patients missing CD4 count data were more often orphans, younger, in poorer health (more malnourished) and were much less likely to receive ART. These patient characteristics were found to be associated with attrition in the literature [24,30,40] and may partly explain our observations. Alternatively, this finding could be reflecting poor access to HIV services among these categories of patients.…”
Section: Discussionsupporting
confidence: 62%
“…For example, patients missing CD4 count data were more often orphans, younger, in poorer health (more malnourished) and were much less likely to receive ART. These patient characteristics were found to be associated with attrition in the literature [24,30,40] and may partly explain our observations. Alternatively, this finding could be reflecting poor access to HIV services among these categories of patients.…”
Section: Discussionsupporting
confidence: 62%
“…Prior studies have shown poorer adherence among double orphans overall with no evidence of differences by gender (14). Although this examination of orphan status was pre-planned, the possibility of type I error must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment adherence is usually monitored by self-report, which poorly reflects true behavior and overestimates adherence [15]. Pill counts have been successfully employed in TB and HIV treatment, but intentional over-distribution pill counts are not widely employed [16][18]. Over-distribution pill counting correlated well with MEMS data, and can identify poorly-adherent patients missed by “correct distribution pill counts,” such as those who discard extra tablets [15], [19].…”
Section: Discussionmentioning
confidence: 99%